2022
DOI: 10.1161/strokeaha.120.032691
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease Susceptibility Gene RNF213 Regulates Endothelial Barrier Function

Abstract: Background: Variants in the ring finger protein 213 ( RNF213 ) gene are known to be associated with increased predisposition to cerebrovascular diseases development. Genomic studies have identified RNF213 as a major risk factor of Moyamoya disease in East Asian descendants. However, little is known about the RNF213 (ring finger protein 213) biological functions or its associated pathogenic mechanisms underlying Moyamoya disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 73 publications
(99 reference statements)
2
26
0
Order By: Relevance
“…When RNF213 was depleted from human cerebral ECs, the authors reported morphological changes associated with increased blood-brain barrier permeability and abnormally high secretion of proinflammatory cytokines. These results suggest that bloodbrain barrier disruption may play a role in MMA and that endothelial dysfunction is the initiating event leading to MMD pathogenesis, as it is in numerous other cerebrovascular diseases [70].…”
Section: Rnf213 Is a Giant Multifunctional Proteinmentioning
confidence: 77%
See 1 more Smart Citation
“…When RNF213 was depleted from human cerebral ECs, the authors reported morphological changes associated with increased blood-brain barrier permeability and abnormally high secretion of proinflammatory cytokines. These results suggest that bloodbrain barrier disruption may play a role in MMA and that endothelial dysfunction is the initiating event leading to MMD pathogenesis, as it is in numerous other cerebrovascular diseases [70].…”
Section: Rnf213 Is a Giant Multifunctional Proteinmentioning
confidence: 77%
“…Together, these studies draw a picture of RNF213 as a multifunctional protein involved in several key cellular processes, including LD stability [57], lipotoxicity [66], WNT [67] and NF-κB signaling, and inflammation [70] (Figure 3). These functions are likely to be related, especially in light of the recently discovered function of RNF213 as a key antimicrobial host protein [56,58].…”
Section: Rnf213 Is a Giant Multifunctional Proteinmentioning
confidence: 99%
“…Furthermore, RNF213 knockout is known to cause inflammatory cytokine secretion in brain endothelium, which is implicated in increased blood–brain barrier permeability, and also inhibits HUVEC angiogenesis, causing delayed cell migration and renewed macrophage migration (Roy et al, 2022; Zhang et al, 2022). In contrast, it was reported that CBL knockdown significantly increased retinal neovascular zones, while CBL overexpression suppressed neovascularization in the retinal tissue of oxygen‐induced retinopathy (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…56 As for vascular permeability, RNF213 could be a key regulator of cerebral endothelium integrity, whose disruption could be an early pathological mechanism leading to MMD. 59 Angiopoietin-1 (Ang-1) and Angiopoietin-2 (Ang-2)…”
Section: Hepatocyte Growth Factormentioning
confidence: 99%